Water-absorbing non-woven fabric and manufacturing process thereof
By utilizing the acid-responsive crosslinking mechanism of core-shell modified zinc oxide with sodium alginate and glucono-δ-lactone, a high-strength gel network was constructed, which solved the shortcomings of absorbent nonwoven fabric in terms of water absorption ratio, wet structural stability and preservation function, and achieved a synergistic effect of efficient water absorption, water retention and long-lasting preservation.
Patent Information
- Application Number
- CN202610345414.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-20
- Publication Date
- 2026-05-15
AI Technical Summary
While maintaining a high absorbency rate, existing absorbent nonwoven fabrics struggle to ensure the stability of the material's wet structure, the durability of its preservation function, and its environmental degradability. Furthermore, the release of active ingredients is uncontrollable in traditional methods.
Modified zinc oxide microparticles with a core-shell structure are combined with sodium alginate and gluconate-δ-lactone to form a high-strength gel network through an acid-responsive crosslinking mechanism. Microcrystalline cellulose is introduced as a dispersant to improve the uniformity of powder distribution and liquid absorption rate, combined with the antibacterial and antioxidant functions of tannic acid.
It achieves a balance between high absorbency and high wet strength, extends the shelf life of fresh produce, significantly improves the storage stability and preservation effect of materials, solves the problems of easy breakage and backflow of traditional absorbent pads, and has a long-lasting preservation function.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of nonwoven fabric technology, specifically to a water-absorbing nonwoven fabric and its manufacturing process. Background Technology
[0002] With the explosive growth of cold chain logistics technology and the fresh food e-commerce industry, consumers are increasingly demanding higher quality standards for fresh products such as meat, seafood, and fruits and vegetables. During the storage and transportation of fresh products, the seepage of tissue fluid (blood) not only damages the packaging appearance but also becomes a breeding ground for bacteria, accelerating food spoilage. Therefore, the market demand for absorbent non-woven fabrics (commonly known as absorbent pads), as a functional packaging material capable of absorbing excess liquid and maintaining a hygienic microenvironment, has increased dramatically.
[0003] Currently, the technical routes for preparing absorbent nonwoven fabrics in the industry mainly focus on the following aspects: The first type is composite materials based on synthetic superabsorbent polymers (SAP). This is currently the mainstream solution in the market, typically involving mixing SAP particles such as sodium polyacrylate with fluff pulp or air-laid paper. Although these materials have extremely high water absorption rates, the SAP particles mainly exist as physical fillers within the fiber network. After absorbing water and swelling, there is a lack of chemical bonds between the particles, resulting in a loose overall structure, resembling a "jelly," with low wet strength. This makes them highly susceptible to cracking, powdering, or liquid backflow when stacked under pressure or during transport, thus contaminating food.
[0004] The second category consists of modified materials based on biomass polysaccharides (such as sodium alginate, chitosan, and cellulose). In response to environmental protection calls and to reduce reliance on petroleum-based SAPs, researchers have attempted to prepare absorbent materials using natural polysaccharides. For example, sodium alginate is used to form a gel based on its ion-exchange properties. However, simple biomass gels typically suffer from slow water absorption rates and fragile gel networks, and their water absorption performance is highly sensitive to environmental pH and ionic strength, making it difficult to completely replace high-performance synthetic resins.
[0005] The third category is functionalized absorbent and preservative materials. To impart additional preservation functions to absorbent pads, current technologies often employ the direct addition of antibacterial agents (such as silver ions, plant extracts, etc.) or antioxidants. While this can inhibit microbial growth to some extent, simple physical mixing often leads to uncontrollable release of active ingredients; either the release is too rapid, resulting in excessively high initial concentrations, or the release is hindered, preventing a long-lasting effect. Furthermore, maintaining high absorbency while simultaneously ensuring the material's mechanical strength and a stable loading of preservative active ingredients remains a significant technical challenge for the industry. In summary, while existing technologies have made some progress in improving water absorption capacity, significant shortcomings remain in balancing various aspects of the material's performance, including water absorption and retention capacity, wet structural stability (strength and toughness), durability of preservation function, and environmental biodegradability. Therefore, developing a bio-based absorbent nonwoven fabric that combines excellent liquid absorption performance, high wet strength and resistance to reverse osmosis, and long-lasting preservation function has significant application value and market prospects. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a water-absorbing nonwoven fabric and its manufacturing process. The present invention overcomes the problems of "storage failure" and "gel brittleness" in ion cross-linking systems through core-shell sustained-release technology. The resulting nonwoven fabric has both a strong and tough water-locking network and excellent antibacterial and antioxidant functions, achieving a synergistic unity of high water absorption, high moisture strength and long-lasting freshness preservation, significantly extending the shelf life of fresh produce.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a water-absorbing nonwoven fabric.
[0008] The absorbent nonwoven fabric comprises a fiber substrate and modified absorbent powder dispersed in the fiber substrate. The modified absorbent powder is not a simple physical mixture, but contains sodium alginate (SA), glucono-δ-lactone (GDL), and modified zinc oxide microparticles with a specific core-shell structure.
[0009] The modified zinc oxide microparticles possess a nanoscale zinc oxide (ZnO) core and a tannic acid-zinc (TA-Zn) coordination shell coating the surface of the core. This core-shell structure is formed in situ by the coordination reaction between the abundant phenolic hydroxyl groups in tannic acid and zinc ions on the zinc oxide surface. This coordination shell, on the one hand, isolates zinc oxide from the external environment (especially direct contact with the acidic component GDL) in a dry state, preventing moisture absorption or premature reaction; on the other hand, it can undergo responsive dissociation under specific acidic conditions after absorbing water, releasing zinc ions and tannic acid molecules.
[0010] As a further improvement of the present invention, the components of the modified water-absorbing powder, by weight parts, include: Sodium alginate: 60-80 parts; Sodium alginate, as the main water-absorbing and gelling matrix, has a G segment (guluronic acid) on its molecular chain that can form an "egg-box" cross-linking structure with divalent metal ions.
[0011] Modified zinc oxide: 10-20 parts; as a crosslinking agent precursor (providing zinc ions) and a multifunctional active ingredient.
[0012] Gluconic acid-δ-lactone: 10~20 parts; as a slow-release acid release agent, it hydrolyzes in water to produce gluconic acid, which lowers the pH of the system, thereby triggering the dissociation of the modified zinc oxide shell and the release of zinc ions.
[0013] Dispersant: 5-30 parts; used to prevent powder from agglomerating during storage and mixing, and to improve the uniformity of powder distribution in fiber matrix.
[0014] Preferably, the dispersant is microcrystalline cellulose (MCC) or wood pulp fiber. Both of these materials are hydrophilic cellulose-based materials, which not only have good dispersion and isolation effects, but also have a certain water absorption capacity. They are compatible with sodium alginate and fiber substrates and will not affect the mechanical properties of the final nonwoven fabric.
[0015] Regarding the selection of fiber substrate, the fiber substrate of this invention is fluff pulp fiber, ES composite fiber (ethylene-propylene parallel or sheath-core composite fiber), or a mixture of the two. Fluff pulp fiber provides the main liquid absorption space and flow channel, while ES composite fiber mainly utilizes its low-melting-point sheath to provide inter-fiber bonding force during hot pressing, maintaining the structural strength of the nonwoven fabric.
[0016] A second aspect of the present invention provides a manufacturing process for the above-mentioned absorbent nonwoven fabric, comprising the following steps: Step (1): Preparation of modified zinc oxide Nano-zinc oxide was dispersed in a solvent, followed by the addition of tannic acid to initiate the reaction. After the reaction was complete, the product was subjected to solid-liquid separation (e.g., centrifugation or vacuum filtration) and dried to obtain the modified zinc oxide with a coordination shell on its surface.
[0017] In this step, to control the thickness and uniformity of the coordination shell, the preferred process conditions are: Solvent system: A mixture of ethanol and water is used, with the volume fraction of ethanol being 30-60%. The addition of ethanol can adjust the solvent polarity, control the solubility of tannic acid and the reaction rate, and is more conducive to film formation.
[0018] Dosage ratio: The ratio of nano zinc oxide to solvent is 1g: 20~50mL; the amount of tannic acid added is 10~50% of the mass of nano zinc oxide. This ratio ensures that the nanoparticles have sufficient dispersion space, while the amount of tannic acid is sufficient to form a complete coating layer.
[0019] Reaction conditions: The reaction temperature is controlled at 25~35℃, and the reaction time is 2~4h. Mild reaction conditions are conducive to the formation of a dense coordination layer and avoid tannic acid oxidation or aggregation caused by high temperature.
[0020] Drying conditions: Drying is carried out at 50~70℃ until constant weight. Too high a temperature may damage the organic coordination structure, while too low a temperature will result in low drying efficiency and residual solvent will affect subsequent processes.
[0021] Step (2): Compounding of modified water-absorbing powder In a dry environment, the modified zinc oxide obtained in step (1) is premixed with a dispersant. The purpose of premixing is to disperse the easily agglomerated modified nanoparticles between larger dispersant particles to prevent them from directly contacting each other.
[0022] Premixing conditions: The mixture should be prepared in an environment with a relative humidity of less than 40% for 5 to 10 minutes.
[0023] Final mixing: Add sodium alginate and gluconate-δ-lactone to the premix and continue mixing until homogeneous for 15-30 minutes.
[0024] Sieving: The mixed powder also includes a step of passing it through a 60-100 mesh sieve to remove any large, damp, agglomerated particles, ensuring uniform particle size and facilitating airflow mesh formation.
[0025] Environmental control: The entire step (2) is strictly controlled to be operated in an environment with a relative humidity of less than 40% because sodium alginate and GDL are both highly hygroscopic substances. Moisture absorption will cause GDL to hydrolyze prematurely or the powder to clump, which will seriously affect the product performance.
[0026] Step (3): Forming of absorbent nonwoven fabric The modified absorbent powder obtained in step (2) is mixed with the fiber substrate through an airflow web forming process to obtain the absorbent nonwoven fabric.
[0027] Formulation: The mass ratio of the modified absorbent powder to the fiber substrate is 3~5:5~7. This ratio range balances the relationship between water absorption capacity (powder contribution), water absorption rate, and structural integrity (fiber contribution).
[0028] Hot pressing treatment: The formed absorbent nonwoven fabric still needs to undergo hot pressing treatment at a temperature of 90~110℃. The main function of hot pressing is to activate the molten bonding of the ES fiber skin, or to enhance the physical entanglement between fibers, fix the position of the powder, prevent the powder from falling off, and control the thickness and density of the nonwoven fabric.
[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The nonwoven absorbent fabric provided by this invention constructs a high-performance liquid absorption system with an "active locking" mechanism by dispersing specific modified absorbent powders in a fiber substrate. Sodium alginate, as the absorbent matrix, has excellent hydrophilicity and gelling ability, forming a high-viscosity gel after liquid absorption, physically blocking water backflow. Glucono-δ-lactone, as an acid-releasing agent, slowly hydrolyzes after water absorption, lowering the pH value of the microenvironment. This not only triggers the gelation chemical reaction, but the slightly acidic environment also has an auxiliary effect in inhibiting microbial growth. The dispersant (microcrystalline cellulose / wood pulp fiber) not only effectively prevents powder agglomeration and ensures the uniform distribution of active components in the nonwoven fabric, but its own hydrophilic liquid-conducting channels can also accelerate the penetration of liquid into the powder, improving the overall liquid absorption rate. More importantly, the above components, combined with modified zinc oxide microparticles, form an "acid-induced in-situ crosslinking" system. When exudate (such as blood from meat) is absorbed, gluconate-δ-lactone releases acid, inducing modified zinc oxide to release zinc ions. The zinc ions rapidly cross-link with the sodium alginate molecular chains, transforming the originally loose physical adsorption into a robust chemical gel network. This significantly improves the gel strength after water absorption, solving the technical problems of traditional absorbent pads being prone to breakage under pressure and backflow, and achieving a balance between high absorbency and high water-locking strength.
[0030] 2. The core innovation of this invention lies in the introduction of modified zinc oxide with a core-shell structure. Through in-situ coordination coating of tannic acid on the surface of nano-zinc oxide, a series of synergistic and beneficial effects are achieved: During dry storage, the dense tannic acid-zinc coordination shell isolates the active zinc oxide core from acidic gluconate-δ-lactone and external moisture, greatly improving the product's storage stability and preventing "pre-condensation" or powder agglomeration. During liquid absorption, the tannic acid molecules released from the acidic environment dissociate the shell, with their long-chain structure and abundant phenolic hydroxyl groups, can form a large number of hydrogen bond networks with sodium alginate molecular chains and flexible coordination bonds with zinc ions. This auxiliary flexible network constructed by "hydrogen bonds and coordination bonds" interweaves within the rigid "sodium alginate-Zn" ion main network, essentially introducing "sacrificial bonds," significantly improving the gel's toughness and elongation at break, effectively solving the problem of high brittleness and easy breakage under pressure in purely ionic cross-linked gels. The released tannins and zinc ions both have excellent antibacterial and antioxidant activities. The two work synergistically to effectively delay the oxidative browning and spoilage of packaged fresh food (especially meat), giving the absorbent nonwoven fabric additional freshness preservation and color protection functions. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Of course, the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0032] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.
[0033] This embodiment provides a water-absorbing nonwoven fabric and its manufacturing process. This water-absorbing nonwoven fabric is particularly suitable for the field of cold chain fresh food packaging, and has excellent liquid absorption and water-locking ability and synergistic preservation function.
[0034] I. Structural Composition of Absorbent Nonwoven Fabric The absorbent nonwoven fabric described in this embodiment mainly consists of two parts: a fiber substrate that serves as a skeleton support, and modified absorbent powder that is uniformly dispersed in the gaps between the fiber substrate.
[0035] 1. Fiber substrate: The fiber substrate is selected from fluff pulp fibers, ES composite fibers (ethylene-propylene parallel or core-sheath composite fibers), or a mixture of both. The fluff pulp fibers provide liquid absorption space, and the ES composite fibers provide thermal bonding strength. In this embodiment, the mass ratio of modified absorbent powder to fiber substrate is controlled between 3~5:5~7 to balance the liquid absorption capacity and the physical strength of the material.
[0036] 2. Modified water-absorbing powder: This powder is an acid-responsive composite functional material, and its components, by weight, include: Sodium alginate (SA): 60-80 parts; Modified zinc oxide: 10-20 parts; Glucono-δ-lactone (GDL): 10-20 parts; Dispersant: 5-30 parts; the dispersant is selected from microcrystalline cellulose or wood pulp fiber.
[0037] The modified zinc oxide is the core component of this invention. It is a core-shell structured microparticle with a core of nano-zinc oxide and a shell formed by interfacial coordination self-assembly of a tannic acid-zinc coordination layer. In the raw materials for preparing these microparticles, the mass ratio of tannic acid to nano-zinc oxide is controlled within the range of 0.1 to 0.5:1 to ensure the formation of a complete and appropriately thick acid-responsive shell.
[0038] II. Manufacturing Process The manufacturing process of the absorbent nonwoven fabric described in this embodiment mainly includes three stages: modified microparticle preparation, dry powder compounding, and core layer forming. The specific steps are as follows: Step (1): Preparation of modified zinc oxide (construction of core-shell structure) First, prepare the reaction solvent. Mix ethanol and water, controlling the volume fraction of ethanol to be 30-60%, to obtain a mixed solvent.
[0039] Nano zinc oxide is added to the above mixed solvent and dispersed by ultrasound or mechanical means. The ratio of nano zinc oxide to solvent is controlled at 1g:20~50mL.
[0040] Subsequently, tannic acid was slowly added to the dispersion. The amount of tannic acid added was strictly controlled to be 10-50% of the mass of the nano-zinc oxide.
[0041] The reaction is carried out under continuous stirring at a temperature of 25-35℃ for 2-4 hours. During this process, tannic acid utilizes its phenolic hydroxyl groups to coordinate with zinc ions on the surface of nano-zinc oxide, thereby growing a dense coordination film in situ.
[0042] After the reaction is complete, the solid product is separated by centrifugation or filtration, and dried to constant weight at 50-70°C. After grinding, the modified zinc oxide is obtained.
[0043] Step (2): Compounding (physical mixing) of modified water-absorbing powder To prevent the components from becoming damp and degraded, this step is carried out entirely in a dry environment with a relative humidity (RH) of less than 40%.
[0044] First, premixing is performed: the modified zinc oxide obtained in step (1) and the dispersant (microcrystalline cellulose or wood pulp fiber) are put into a mixer and mixed for 5-10 minutes. This step uses the dispersant to separate the nanoparticles and prevent agglomeration.
[0045] Then perform final mixing: add the prescribed amounts of sodium alginate and gluconate-δ-lactone to the premix, and continue mixing for 15-30 minutes until all components are evenly dispersed.
[0046] After mixing, the resulting powder is passed through a 60-100 mesh sieve to remove any possible agglomerates, thus obtaining a modified water-absorbing powder with uniform particle size.
[0047] Step (3): Airflow web formation and hot pressing The modified absorbent powder prepared in step (2) is mixed and shaped with the fiber substrate (fluff pulp / ES fiber) using an airflow web forming device. By adjusting the feeding speed, the ratio of powder to fiber is controlled within the range of 3~5:5~7 to form a uniform fiber web layer.
[0048] Finally, the fiber web layer is fed into a hot pressing device for hot pressing treatment. The hot pressing temperature is controlled at 90~110℃. At this temperature, the outer layer of the ES fiber melts and generates adhesive force, firmly locking the absorbent powder in the fiber network. After cooling and slitting, the finished absorbent nonwoven fabric is obtained.
[0049] When the absorbent nonwoven fabric prepared by the above process comes into contact with blood seeping from fresh meat (usually with a weakly acidic or neutral pH), the GDL in the powder will slowly hydrolyze and further acidify the environment, inducing the dissociation of the shell layer on the surface of modified zinc oxide. The released zinc ions will quickly undergo a cross-linking reaction with sodium alginate to form a high-strength gel. At the same time, the released tannic acid will help to build a flexible network and provide antioxidant and color-protecting functions.
[0050] The present invention will be further described below through specific embodiments.
[0051] Example 1
[0052] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Prepare a mixed solvent by mixing ethanol and deionized water at a volume ratio of 1:1.5 (ethanol volume fraction is 40%). Weigh 5g of nano zinc oxide and add it to 150mL of the above mixed solvent (volume ratio 1g:30mL), and mechanically stir to disperse it evenly. Then, weigh 1.5g of tannic acid (tannic acid to nano zinc oxide mass ratio is 0.3:1) and slowly add it to the dispersion, and stir continuously at 30℃ for 3 hours. After the reaction is completed, centrifuge the mixture, collect the solid precipitate, dry it in an oven at 60℃ to constant weight, and grind it to obtain modified zinc oxide.
[0053] (2) Control the relative humidity of the environment at 35%. First, weigh 15 parts (by weight, the same below) of the modified zinc oxide prepared above and 20 parts of microcrystalline cellulose and put them into a mixer, and premix for 8 minutes. Then, add 70 parts of sodium alginate and 15 parts of glucono-δ-lactone to the mixer and continue mixing for 20 minutes. Pass the uniformly mixed powder through an 80-mesh sieve, collect the sieve residue, and obtain the modified water-absorbing powder.
[0054] (3) Fluff pulp fiber is selected as the fiber substrate. The modified absorbent powder and fluff pulp fiber are mixed and formed into a web using an air-flow web forming device, and the mass ratio of modified absorbent powder to fluff pulp fiber is controlled to be 4:6. The formed web is fed into a hot press roller for hot pressing treatment. The hot pressing temperature is set to 100℃. After hot pressing, it is cooled and cut to obtain the absorbent nonwoven fabric.
[0055] Example 2
[0056] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Mix ethanol and deionized water to make the ethanol volume fraction 30%. Weigh out nano zinc oxide and add it to the solvent at a ratio of 1g:20mL, and disperse it evenly. Add tannic acid at a mass ratio of 0.1:1 to nano zinc oxide. Stir the reaction at 25℃ for 4 hours. After the reaction is complete, centrifuge and dry at 50℃ to constant weight to obtain modified zinc oxide.
[0057] (2) Control the relative humidity of the environment at 30%. Weigh 20 parts of the above modified zinc oxide and 5 parts of wood pulp fiber (dispersant) and premix for 5 minutes. Then add 60 parts of sodium alginate and 20 parts of gluconate-δ-lactone, and continue mixing for 15 minutes. Pass the mixed powder through a 60-mesh sieve to obtain modified water-absorbing powder.
[0058] (3) A mixture of fluff pulp fiber and ES composite fiber (mass ratio 1:1) was selected as the fiber substrate. The powder and fiber were mixed by air-flow web forming at a mass ratio of 3:7. The hot pressing temperature was set to 90℃ to obtain the absorbent nonwoven fabric.
[0059] Example 3
[0060] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Mix ethanol and deionized water to make the ethanol volume fraction 60%. Weigh out nano zinc oxide and add it to the solvent at a ratio of 1g:50mL, and disperse it evenly. Add tannic acid at a mass ratio of 0.5:1 to nano zinc oxide. Stir the reaction at 35℃ for 2 hours. After the reaction is complete, centrifuge and dry at 70℃ to constant weight to obtain modified zinc oxide.
[0061] (2) Control the relative humidity of the environment at 38%. Weigh 10 parts of the above modified zinc oxide and 30 parts of microcrystalline cellulose and premix for 10 minutes. Then add 80 parts of sodium alginate and 10 parts of glucono-δ-lactone, and continue mixing for 30 minutes. Pass the mixed powder through a 100-mesh sieve to obtain modified water-absorbing powder.
[0062] (3) Fluff pulp fiber was selected as the fiber substrate. The powder and fiber were mixed by air-flow web forming at a mass ratio of 5:5. The hot pressing temperature was set to 110℃ to obtain the absorbent nonwoven fabric.
[0063] Example 4
[0064] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Modified zinc oxide was prepared using the same process steps and parameters as in Example 1.
[0065] (2) Control the relative humidity of the environment at 35%. Weigh 15 parts of the above-mentioned modified zinc oxide and 20 parts of wood pulp fiber (to replace microcrystalline cellulose) and premix for 8 minutes. Then add 70 parts of sodium alginate and 15 parts of gluconate-δ-lactone, and continue mixing for 20 minutes. Pass through an 80-mesh sieve to obtain modified water-absorbing powder.
[0066] (3) ES composite fiber (replacing fluff pulp fiber) was selected as the fiber substrate. The powder and fiber were mixed by air-jet forming at a mass ratio of 4:6. The hot pressing temperature was set to 105℃ to obtain the absorbent nonwoven fabric.
[0067] Comparative Example 1
[0068] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) The liquid-phase reaction preparation step of modified zinc oxide is omitted. Untreated nano zinc oxide powder and tannic acid powder are prepared directly.
[0069] (2) Control the relative humidity of the environment at 35%. Weigh 11.5 parts of nano zinc oxide, 3.5 parts of tannic acid powder (total weight 15 parts, corresponding to the proportion in Example 1) and 20 parts of microcrystalline cellulose and mix them. Then add 70 parts of sodium alginate and 15 parts of glucono-δ-lactone and mix evenly. Pass through an 80-mesh sieve to obtain the mixed powder.
[0070] (3) Nonwoven fabric was prepared using the same fiber substrate and web forming and hot pressing process as in Example 1 (powder to fiber ratio 4:6, hot pressing 100℃).
[0071] Comparative Example 2
[0072] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Prepare unmodified nano zinc oxide powder without any tannic acid treatment.
[0073] (2) Control the relative humidity of the environment at 35%. Weigh 15 parts of unmodified nano zinc oxide and 20 parts of microcrystalline cellulose and premix. Then add 70 parts of sodium alginate and 15 parts of gluconate-δ-lactone and mix evenly. Pass through an 80-mesh sieve to obtain the mixed powder.
[0074] (3) Nonwoven fabric was prepared using the same fiber substrate and web forming and hot pressing process as in Example 1.
[0075] Comparative Example 3
[0076] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Modified zinc oxide was prepared using the same process as in Example 1.
[0077] (2) Control the relative humidity of the environment at 35%. Weigh 15 parts of modified zinc oxide and 35 parts of microcrystalline cellulose (15 parts were added to make up the total amount) and premix. Then add 70 parts of sodium alginate, without adding glucono-δ-lactone, and mix evenly. Pass through an 80-mesh sieve to obtain the mixed powder.
[0078] (3) Nonwoven fabric was prepared using the same fiber substrate and web forming and hot pressing process as in Example 1.
[0079] Comparative Example 4
[0080] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Prepare micron-sized calcium carbonate powder and tannic acid powder.
[0081] (2) Control the relative humidity of the environment at 35%. Weigh 11.5 parts of calcium carbonate powder, 3.5 parts of tannic acid powder (replacing 15 parts of modified zinc oxide in Example 1) and 20 parts of microcrystalline cellulose and mix them. Then add 70 parts of sodium alginate and 15 parts of glucono-δ-lactone and mix evenly. Pass through an 80-mesh sieve to obtain the mixed powder.
[0082] (3) Nonwoven fabric was prepared using the same fiber substrate and web forming and hot pressing process as in Example 1.
[0083] Comparative Example 5
[0084] A manufacturing process for a water-absorbing nonwoven fabric includes the following steps: (1) Prepare commercially available superabsorbent polymer (SAP, sodium polyacrylate granules).
[0085] (2) Control the relative humidity of the environment at 35%. Weigh 85 parts of SAP particles (to replace the total amount of SA, ZnO and GDL) and mix them evenly with 35 parts of microcrystalline cellulose.
[0086] (3) Nonwoven fabric was prepared using the same fiber substrate and web forming and hot pressing process as in Example 1.
[0087] I. Experimental Test Items and Methods 1. Liquid absorption and water retention capacity test Test method: Refer to ISO 11948-1 standard. Cut nonwoven fabric samples of the same area (10cm × 10cm) for each embodiment and comparative example, and weigh them (W0). Immerse them in 0.9% physiological saline (simulating the osmotic pressure of meat exudate) for 30 minutes, remove them, hang them to drain for 2 minutes, and weigh them (W1). Then place the water-saturated samples in a centrifuge and centrifuge at 1400 r / m for 3 minutes (simulating a pressure environment), remove them, and weigh them (W2).
[0088] Calculation formula: Saturation absorption rate = (W1 - W0) / W0 Centrifugal water retention ratio = (W2 - W0) / W0 2. Wet gel strength test Test objective: To verify whether the flexible network introduced by tannic acid improves the brittleness of the ionic crosslinked gel.
[0089] Test method: After the sample is saturated with water into a gel state, it is cut into strips 2 cm wide. A tensile test is performed using a universal testing machine at a tensile speed of 50 mm / min. The elongation at break (%) and wet tensile strength (N) are recorded. Higher values indicate a stronger and tougher gel network, making it less prone to rupture and backflow under pressure.
[0090] 3. Storage stability test Test method: All samples were placed in a constant temperature and humidity chamber for accelerated aging (conditions: temperature 45℃, relative humidity 75%, duration 7 days). After aging, the above "centrifugal water retention ratio" test was repeated.
[0091] Indicator: Performance retention rate = (water retention ratio after aging / water retention ratio of fresh sample) × 100%. A low retention rate indicates that the powder has prematurely absorbed moisture during storage ("pre-condensation"), resulting in severe failure.
[0092] 4. Fresh Produce Preservation Effect Test Test method: Prepare fresh chilled pork and cut it into 50g pieces. Place them separately on trays lined with absorbent pads from different embodiments / comparative examples, seal with plastic wrap, and store in a refrigerator at 4°C.
[0093] Indicator: On the 5th day, the pork was removed and the volatile basic nitrogen (TVB-N) content (mg / 100g) was measured. TVB-N is a key indicator of meat spoilage; the lower the value, the better the preservation effect (the national standard GB 2707-2016 stipulates that fresh meat with TVB-N ≤ 15 is qualified).
[0094] II. Experimental Data Table Table 1 Comparison of performance test results between each embodiment and the comparative example
[0095] III. Data Analysis and Conclusions 1. Stability of the "core-shell structure" (Example 1 vs. Comparative Example 1 and Comparative Example 2): Example 1 showed a performance retention rate of up to 96.5% after aging, while Comparative Example 1 with simple physical mixing had a retention rate of only 41.2%, and Comparative Example 2 without a shell had a retention rate of 35.5%.
[0096] This demonstrates that the core technical feature of this invention—the "coordination shell formed by in-situ reaction"—effectively isolates zinc oxide from acidic components (GDL) and ambient moisture. Comparative Example 1, although having the same composition, failed to form a dense shell, resulting in premature reaction between GDL and ZnO during storage and subsequent failure upon use.
[0097] 2. The toughening synergistic effect of "tannic acid-zinc" (Example 1 vs. Comparative Example 2, Comparative Example 4): The wet strength of Example 1 (18.4 N) was significantly higher than that of Comparative Example 2 (6.5 N) without tannins and Comparative Example 4 (11.5 N) of the calcium system.
[0098] In Comparative Example 2, the simple Zn-SA crosslinking was too rigid and easily broken under stress (high brittleness); while in Example 1, the released tannic acid formed hydrogen bonds with SA and flexible coordination bonds with Zn, constructing a "sacrificial bond" network, which greatly improved the toughness of the gel. At the same time, this also proves that the "zinc-tannic acid" system has a stronger structural induction ability than the "calcium-tannic acid" system (Comparative Example 4).
[0099] 3. “Active cross-linking” is superior to “physical adsorption” (Example 1 vs. Comparative Example 3, Comparative Example 5): Comparative Example 3, which lacks GDL, has an extremely low water retention ratio (8.4), indicating that there is no acid release, cross-linking cannot be triggered, and water cannot be locked in. Although ordinary SAP (Comparative Example 5) has a high water absorption ratio (35.0), its wet strength is extremely low (2.5N), it is loose and jelly-like, and has no preservation ability (TVB-N is as high as 22.4).
[0100] This demonstrates that the "acid-induced crosslinking" mechanism of this invention achieves a balance between high water absorption and high strength, and has irreplaceable functionality compared to traditional materials.
[0101] 4. Functionality of "antibacterial and preservation" (Example 1 vs. Comparative Example 2, Comparative Example 4, Comparative Example 5): The pork treated in Example 1 had the lowest TVB-N value (11.2), which was better than Comparative Example 2 (16.8, only Zn without TA) and Comparative Example 4 (17.6, with TA but no Zn).
[0102] This demonstrates that Zn ions and tannic acid have synergistic antibacterial and antioxidant effects. Neither is dispensable: the effect of Zn alone or TA alone is not as good as the combination of the two (Example 1), and the preservation ability of the calcium system (Comparative Example 4) is significantly weaker than that of the zinc system.
[0103] The experimental data above fully verify that the technical solution of the present invention has high stability, high wet strength and excellent preservation function, and that there is a significant synergistic effect among the components.
[0104] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A water-absorbing nonwoven fabric, characterized in that, Includes a fiber substrate and modified water-absorbing powder dispersed in the fiber substrate; The modified water-absorbing powder comprises sodium alginate, gluconate-δ-lactone, and core-shell structured modified zinc oxide microparticles; wherein the modified zinc oxide microparticles have a nano zinc oxide core and a tannic acid-zinc coordination shell coating the surface of the core.
2. The absorbent nonwoven fabric according to claim 1, characterized in that, The modified absorbent powder comprises, by weight, 60-80 parts sodium alginate, 10-20 parts modified zinc oxide, 10-20 parts glucono-δ-lactone, and 5-30 parts dispersant.
3. The absorbent nonwoven fabric according to claim 2, characterized in that, The dispersant is microcrystalline cellulose or wood pulp fiber.
4. The absorbent nonwoven fabric according to claim 1, characterized in that, The fiber substrate is fluff pulp fiber, ES composite fiber, or a mixture of the two.
5. A manufacturing process for the absorbent nonwoven fabric according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Add nano zinc oxide to a solvent to disperse it, then add tannic acid to react, and after the reaction is completed, separate the solid and liquid and dry it to obtain the modified zinc oxide; (2) First, the modified zinc oxide is premixed with the dispersant, and then sodium alginate and gluconate-δ-lactone are added and mixed evenly to obtain the modified water-absorbing powder; (3) The modified water-absorbing powder and the fiber substrate are mixed and formed by airflow web forming process to obtain the water-absorbing nonwoven fabric.
6. The manufacturing process according to claim 5, characterized in that, In step (1), the solvent is a mixture of ethanol and water, and the volume fraction of ethanol in the mixture is 30-60%; the ratio of nano zinc oxide to solvent is 1g:20-50mL; and the amount of tannic acid added is 10-50% of the mass of nano zinc oxide.
7. The manufacturing process according to claim 5, characterized in that, In step (1), the reaction temperature is 25~35℃ and the reaction time is 2~4h.
8. The manufacturing process according to claim 5, characterized in that, In step (1), drying is performed at 50~70℃ until constant weight.
9. The manufacturing process according to claim 5, characterized in that, In step (2), the premixing is carried out in an environment with a relative humidity of less than 40%, and the premixing time is 5 to 10 minutes. After adding sodium alginate and gluconate-δ-lactone, the mixing time is 15 to 30 minutes. The mixing process also includes passing the mixture through a 60 to 100 mesh sieve.
10. The manufacturing process according to claim 5, characterized in that, In step (3), the mass ratio of the modified absorbent powder to the fiber substrate is 3~5:5~7; the formed absorbent nonwoven fabric is also subjected to hot pressing treatment at a temperature of 90~110℃.